Application of APACHE II scoring system in assessing prognosis of critically ill surgical and trauma patients - C. S., Chandan; Kumar, Mohan; S., Sudarsan (International Surgery Journal, 2018)
Background: Surgical patients who become critically ill almost always fall in to one of the three categories: major trauma, major surgery or sepsis. In all three patient categories the patho-physiological processes that make patients ill and lead to cellular injury and organ dysfunction are essentially same, and therefore the way that patients need support of critical organ function are same. Surgical complications remain a frustrating and difficult aspect of operative treatment of patients, regardless of how technically gifted, skilled and capable surgeons. Various critical care and outcome scoring systems are used for outcome assessment of surgical patients. Using scores like APACHE II at the admission and SOFA on admission and also in their due course may help in predicting outcome. Methods: This study included 50 patients studied for a patient for 1 year. The clinical profile of 50 patients with sepsis with MODS was studied. There were 28 males and 22 females in this cohort. Results: In this study, 18 patients died, and 32 patients survived with mortality rate of 36%. In this study also, mean APACHE II score was high among non-survivors than survivors (27.67 v/s 16.00), which score was suggestive of statistical significance (p<0.001). The APACHE II score on day of admission, though reliable, was less effective in predicting the mortality rate in our set up. Conclusions: The APACHE II score on day of admission, though reliable, was less effective than SOFA score in predicting the mortality rate